Detecting ecological impacts concepts and applications in coastal habitats - Schmitt, Russell J.; Osenberg, Craig W. (San Diego : Academic Press, 1996)
Detecting Ecological Impacts: Concepts and Applications in Coastal Habitats focuses on crucial aspects of detecting local and regional impacts that result from human activities. Detection and characterization of ecological impacts require scientific approaches that can reliably separate the effects of a specific anthropogenic activity from those of other processes. This fundamental goal is both technically and operationally challenging. Detecting Ecological Impacts is devoted to the conceptual and technical underpinnings that allow for reliable estimates of ecological effects caused by human activities. An international team of scientists focuses on the development and application of scientific tools appropriate for estimating the magnitude and spatial extent of ecological impacts. The contributors also evaluate our current ability to forecast impacts. Some of the scientific, legal, and administrative constraints that impede these critical tasks also are highlighted. Coastal marine habitats are emphasized, but the lessons and insights have general application to all ecological systems.
Estimating the size of an effect from a before-after-control-impact paired series design: the predictive approach applied to a power plant study / James R. Bence, Allan Stwart-Oaten, and Stephen C. Schroeter -- On beyond BACI: sampling designs that might reliably detect environmental disturbances -- Determining the spatial extent of ecological impacts caused by local anthropogenic distribances in coastal marine habitats / Peter T. Raimondi and Daniel C. Reed -- Predicting the scale of marine impacts: understanding planktonic links between populations / Michael J. Keough and Kerry P. Black -- Influence of pollutants and oceanography on abundance and deformities of wild fish larvae / Michael J. Kingsford and Charles A. Gray -- Consequences for adult fish stocks of human-induced mortality on immatures / Roger M. Nisbet, William W. Murdoch, and Allan Stewart-Oaten -- The art and science of administrative environmental impact assessment / Russell J. Schmitt, Craig W. Osenberg, etc ... -- On the adequacy and improvement of marine benthic pre-impact surveys: examples from the Gulf of Mexico outer continental shelf / Robert S. Carney -- Organizational constraints on environmental impact assessment research / Frederick M. Piltz -- Administrative, legal, and public policy constraints on environmental impact assessment / Charles Lester -- Predicted on observed environmental impacts: can we foretell ecological change? / Richard F. Ambrose, Russell J. Schmitt, and Craig W. Osenberg.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Ecological risk assessment; Environmental monitoring; Coastal ecology; Environnement -- Surveillance; Electronic books